2018
DOI: 10.1002/ccd.27846
|View full text |Cite
|
Sign up to set email alerts
|

Transradial left gastric artery embolization to treat severe obesity: A pilot study

Abstract: Background Bariatric surgery is currently the only effective treatment with long‐lasting results to treat severe obesity. Objectives We performed a pilot study to evaluate the feasibility, safety and efficacy of percutaneous distal embolization of the left gastric artery (LGA) using a transradial approach. Methods and Results We recruited seven severely obese male patients (mean age 48 ± 7 years) referred for diagnostic coronary angiography. Mean baseline weight was 160 ± 27 kg and body mass index was of 52 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
(67 reference statements)
1
24
0
Order By: Relevance
“…A statistically significant correlation between BMI and HbA1c was made (r ¼ 0.91); however, no definite conclusions can be drawn due to sample size and other study limitations. This study, utilizing femoral access to achieve BAE, reported similar procedure and fluoroscopy times (25.3 AE 6.3 and 15.5 AE 4.4 minute) as Pirlet et al 114 indicating that BAE can be performed in a timely manner irrespective of the access site chosen. Mild adverse events were only seen in seven study participants reporting mild postprocedural epigastric pain that resolved within 24 hours.…”
Section: Clinical Investigationssupporting
confidence: 64%
See 1 more Smart Citation
“…A statistically significant correlation between BMI and HbA1c was made (r ¼ 0.91); however, no definite conclusions can be drawn due to sample size and other study limitations. This study, utilizing femoral access to achieve BAE, reported similar procedure and fluoroscopy times (25.3 AE 6.3 and 15.5 AE 4.4 minute) as Pirlet et al 114 indicating that BAE can be performed in a timely manner irrespective of the access site chosen. Mild adverse events were only seen in seven study participants reporting mild postprocedural epigastric pain that resolved within 24 hours.…”
Section: Clinical Investigationssupporting
confidence: 64%
“…Significant variability existed among the inclusion criteria of the different studies discussed in this review. For example, the average patient BMI of patients included in the studies ranged from 28.9 kg/m 2 seen in Elens et al 110 to 52 kg/m 2 seen in Pirlet et al 114 Although there was no statistically significant correlation between patient BMI and achieved weight loss in the recent meta-analysis (cite), it is likely that future studies with increased power will shed additional light on the ideal BMI range to consider BAE.…”
Section: Discussion/future Directionsmentioning
confidence: 94%
“…Mean weight loss percentage and mean weight loss in kilograms for each study are mentioned in Table 2. A study by Pirlet et al was the only study included that had 100% of morbidly obese male participants whereas, in the study by Kipshidze et al, males made up 80% of the participants; these two studies have a slightly higher percentage of weight loss compared to the other prospective studies included [25,28]. A study by Elen et al was the only clinical trial studied the LGE in overweight participants with a mean baseline BMI of 27.4 kg, resulting in 10% weight loss of their total body mass [32].…”
Section: The Efficiency Of Left Gastric Artery Embolizationmentioning
confidence: 97%
“…But, what if you could lose weight on the order of 10 kg with a procedure done through your radial artery that took only 25 min? Drive through weight loss; this might seem too good to be true, but in this issue of the Journal, Pirlet et al, present their initial experience with just such procedure …”
mentioning
confidence: 99%
“…Embolization of the left gastric artery in both animal and humans results in an acute drop in ghrelin and in many cases subsequent weight loss. As a pilot study, the investigators embolized the left gastric artery in seven morbidly obese men. All procedures were done via the radial artery to eliminate the risk of vascular access bleeding that is a real risk in very obese patients.…”
mentioning
confidence: 99%